Does a complex intervention increase patient knowledge about oral anticoagulation? - a cluster-randomised controlled trial. Issue 1 (December 2017) - Maikranz, Verena; Siebenhofer, Andrea; Ulrich, Lisa-R.; Mergenthal, Karola; Schulz-Rothe, Sylvia; Kemperdick, Birgit; Rauck, Sandra; Pregartner, Gudrun; Berghold, Andrea; Gerlach, Ferdinand; Petersen, Juliana
Abstract Background Oral anticoagulation therapy (OAT) is a challenge in general practice, especially for high-risk groups such as the elderly. Insufficient patient knowledge about safety-relevant aspects of OAT is considered to be one of the main reasons for complications. The research question addressed in this manuscript is whether a complex intervention that includes practice-based case management, self-management of OAT and additional patient and practice team education improves patient knowledge about anticoagulation therapy compared to a control group of patients receiving usual care (as a secondary objective of the Primary Care Management for Optimised Antithrombotic Treatment (PICANT) trial). Methods The cluster-randomised controlled PICANT trial was conducted in 52 general practices in Germany, between 2012 and 2015. Trial participants were patients with a long-term indication for oral anticoagulation. A questionnaire was used to assess knowledge at baseline, after 12, and after 24 months. The questionnaire consists of 13 items (with a range of 0 to 13 sum-score points) covering topics related to intervention. Differences in the development of patient knowledge between intervention and control groups compared to baseline were assessed for each follow-up by means of linear mixed-effects models. Results Seven hundred thirty-six patients were included at baseline, of whom 95.4% continued to participate after 12 months, and 89.3% after 24 months. The average age of patients was 73.5 years (SD 9.4), and they mainly suffered from atrial fibrillation (81.1%). Patients in the intervention and control groups had similar knowledge about oral anticoagulation at baseline (5.6 (SD 2.3) in both groups). After 12 months, the improvement in the level of knowledge (compared to baseline) was significantly larger in the intervention group than in the control group (0.78 (SD 2.5) vs. 0.04 (SD 2.3);p = 0.0009). After 24 months, the difference between both groups was still statistically significant (0.6 (SD 2.6) vs. -0.3 (SD 2.3);p = 0.0001). Conclusion Since this intervention was effective, it should be established in general practice as a means of improving patient knowledge about oral anticoagulation. Trial registration Current controlled trialsISRCTN41847489 ; Date of registration: 13/04/2012